2013
DOI: 10.1097/hjh.0b013e32835c5c23
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-ankle pulse wave velocity predicts the development of cardiovascular disease in a general Japanese population

Abstract: Our findings suggest that brachial-ankle pulse wave velocity is a significant predictive factor for cardiovascular disease in the general Japanese population and that information on brachial-ankle pulse wave velocity substantially improves cardiovascular risk assessment beyond that achieved by a model based on potential risk factors in general practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 27 publications
0
78
0
Order By: Relevance
“…Because baPWV is non-invasive, convenient to measure, and requires little technical expertise, it is widely available. Both cfPWV and baPWV have been shown to be strong predictors of clinically evident CVD events [12][13][14][15][16][17] . However, few populationbased observational studies have documented a link between either measurement and subclinical atherosclerosis, including CAC 18,19) .…”
Section: Blood Testmentioning
confidence: 99%
“…Because baPWV is non-invasive, convenient to measure, and requires little technical expertise, it is widely available. Both cfPWV and baPWV have been shown to be strong predictors of clinically evident CVD events [12][13][14][15][16][17] . However, few populationbased observational studies have documented a link between either measurement and subclinical atherosclerosis, including CAC 18,19) .…”
Section: Blood Testmentioning
confidence: 99%
“…9 Particularly relevant to this report, recent longitudinal studies have demonstrated that increased baPWV levels predict cardiovascular mortality and morbidity among high-risk patients and the general population. [10][11][12][13] In their current guidelines on the management of arterial hypertension, the European Society of Hypertension mentioned PWV as a potential consideration in managing middle-aged hypertensive patients with increased aortic stiffness.…”
Section: Song Et Al Bapwv and Bp Control Predict First Incident Strokmentioning
confidence: 99%
“…We excluded 5506 subjects from the analyses (the details of the exclusions and inaccurate baPWV measurement 25 are described in Appendix S1 in the online-only Data Supplement). A final total of 13 381 subjects from 7 cohorts were included in the analysis for all-cause mortality (5 published studies 12,13,15,17,18 and 2 unpublished studies 14,16 ), and 14 673 participants from 8 studies (5 published studies 12,13,15,17,18 and 3 unpublished studies 11,14,16 ) were included in the analysis for CVD risk.…”
Section: Study Populationmentioning
confidence: 99%
“…This collaborative study included the data from 14 cohort studies conducted in Japan (9 published and 5 unpublished studies). [11][12][13][14][15][16][17][18][19][20][21][22][23][24] The study was conducted with the approval of the Ethical Guidelines Committee of Tokyo Medical University (No 2655. Figure 1 depicts the process used to select the study population.…”
Section: Study Populationmentioning
confidence: 99%